2013
DOI: 10.1124/jpet.113.205120
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Antiproliferative Effects of the Aminoalkylindole WIN55,212-2 and Radiation in Breast Cancer Cells

Abstract: The potential antitumor activity of cannabinoid receptor agonists, such as the aminoalklylindole WIN55,212-2 (WIN2), has been studied extensively, but their potential interaction with conventional cancer therapies, such as radiation, remains unknown. In the present work, the influence of WIN2 on the antiproliferative activity of radiation in human (MCF-7 and MDA-MB231) and murine (4T1) breast cancer cells was investigated. The antiproliferative effects produced by combination of WIN2 and radiation were more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Emery et al investigated the effects of THC and CBD to modulate the growth inhibitory effects of radiation in breast cancer cell lines in culture. Both cannabinoids did not alter the anti-proliferative effects of radiation (Emery et al, 2014). However, recent studies have evaluated the efficacy of CBD, THC or combinations thereof to enhance the anti-tumor effect of radiation using an immunocompetent orthotopic murine glioma model.…”
Section: Cannabinoids In Combination With First-line Therapiesmentioning
confidence: 94%
“…Emery et al investigated the effects of THC and CBD to modulate the growth inhibitory effects of radiation in breast cancer cell lines in culture. Both cannabinoids did not alter the anti-proliferative effects of radiation (Emery et al, 2014). However, recent studies have evaluated the efficacy of CBD, THC or combinations thereof to enhance the anti-tumor effect of radiation using an immunocompetent orthotopic murine glioma model.…”
Section: Cannabinoids In Combination With First-line Therapiesmentioning
confidence: 94%
“…In ER Ϫ breast cancer cells, S1P 4 expression activated the ERK1/2 pathway and correlated with poor prognosis ( 167 ). In vitro, several breast cancer cell lines respond to S1P or S1P 1 agonist SEW2871 with increased proliferation ( 168 ).…”
Section: Nervous Systemmentioning
confidence: 99%
“…Recent studies have shown that WIN can inhibit cell proliferation in many tumour types . So we first detected the cell viability of osteosarcoma Saos‐2 cells treated by WIN.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that WIN can inhibit cell proliferation in many tumour types. 3,4 So we first detected the cell viability of osteosarcoma Saos-2 cells treated by WIN. Our result showed that the proliferation of Saos-2 cells was inhibited by WIN in a dose-dependent and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation